2021
DOI: 10.22541/au.162798844.49257233/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PDW as an İnflammation Marker in Primary Hyperparathyroi̇di̇sm

Abstract: Aims Primary hyperparathyroidism (PHPT) is common disorder in which parathyroid hormone (PTH) is excessively secreted from one or more of four parathyroid glands. Primary hyperparathyroidism (PHPT) is an endocrinological disorder associated with increased systemic inflammation, endothelial dysfunction. The systemic inflammation may cause subclinical decrease in cardiac function. Our aim in our study is to compare the markers of systemic inflammation in preoperative, postoperative period with PHPT, to show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…PDW is obtained by analyzing the size distribution curve of platelets, with the width at the 20% level being defined as PDW ( 42 ). A retrospective study of patients with PHPT revealed a significant elevation in the preoperative PDW value when compared to both the postoperative period and control groups ( 43 ). These outcomes are in line with what our study revealed.…”
Section: Discussionmentioning
confidence: 99%
“…PDW is obtained by analyzing the size distribution curve of platelets, with the width at the 20% level being defined as PDW ( 42 ). A retrospective study of patients with PHPT revealed a significant elevation in the preoperative PDW value when compared to both the postoperative period and control groups ( 43 ). These outcomes are in line with what our study revealed.…”
Section: Discussionmentioning
confidence: 99%